Late Weichselian and Holocene glacier dynamics and sedimentary processes in and north of the Wijdefjorden-Austfjorden fjord system, north Spitsbergen - Braun, Carmen (UiT Norges arktiske universitet, 2019)
Multi-proxy analyses (lithostratigraphy, physical properties, XRF core scanning, and grain size analysis) of five sediment cores and high resolution seismic (chirp) data were integrated to reconstruct the Late Weichselian and Holocene sedimentary environments and glacial history in and on the shelf north of Wijdefjorden. Three acoustic units (U1-U3) correlating with three lithostratigraphic units (L1-L3) are defined. A glacial till (U1/L1) covers most of the area, though it is sometimes lost over bedrock highs and is not visible beneath thicker sediment sequences. The overlying sediments are divided into two units representing glacier-proximal (U2/L2) and -distal (U3/L3) glaciomarine depositional settings. Both tend to drape the underlying till. Suspension settling from meltwater plumes and rivers is the primary source of such sediments. The origin of the suspended sediments fluctuates in the glacier-proximal sediments; laminations of sediments with different colours, densities, and element ratios reflect sources in either the southwest and Woodfjorden, or in the northwest and east of Wijdefjorden. The glacier-distal sediments are massive, indicating a greater distance from fluctuating sources and more stable conditions. Sediments from the southwest have a greater influence in the inner fjord, while and sediments from the east are more important in the outer fjord . In the central fjord sediments derived from both sides are important. Beyond the mouth of the fjord, sediments from Woodfjorden are present. The glaciomarine sediments also have IRD-rich (ice rafted debris) intervals in the cores, which generally correlate with internal reflections in the chirp profile and reflect periods of enhanced sea ice rafting. The deglaciation of the shelf likely occurred before ~16 cal. ka BP, and the presence of IRD on the shelf after ~14.8 cal. ka BP likely indicates the beginning of the retreat of ice into the fjords. The transition from glacier-proximal to -distal sedimentation on the shelf, signalling a weakening glacial ...